Gender, competition and the efficiency of policy interventions - Loukas Balafoutas; Matthias Sutter (University of Innsbruck, Department of Public Finance, 2010)
Recent research has shown that women shy away from competition more often than men. We evaluate experimentally three alternative policy interventions to promote women in competitions: Quotas, Preferential Treatment, and Repetition of the Competition unless a critical number of female winners is reached. We find that Quotas and Preferential Treatment encourage women to compete significantly more often than in a control treatment, while efficiency in selecting the best candidates as winners is not worse. The level of cooperation in a post-competition teamwork task is even higher with successful policy interventions. Hence, policy measures promoting women can have a double dividend.
Keywords: C91; D03; 330; Competition; gender gap; experiment; affirmative action; teamwork; coordination; Verhaltensökonomik; Wettbewerb; Geschlecht; Frauenpolitik; Arbeitsgruppe; Test